Cladistic, biogeographic and environmental niche analysis of the species of Agathemera Stål (Phasmatida, Agathemeridae) - Dominguez, M. Cecilia; San Blas, German; Agrain, Federico; Roig-Juñent, Sergio A.; Scollo, Ana M.; Debandi, Guillermo O. (Zootaxa, 2009)
The endemic southern South American genus Agathemera Stål, which contains eight species, is analyzed in a cladistic context in order to establish a hypothesis regarding the phylogenetic relationships among its species. The cladistic analysis is based on adult and immature morphological characters belonging to both sexes. A biogeographical analysis is also performed to reconstruct the biogeographic history of the genus, and an environmental niche analysis to determine the potential distribution of the species, estimate niche overlap among species, and to find the most important variables that explain its present distribution. One tree of 51 steps was obtained that supports the monophyly of the genus. The species A. elegans and A. mesoauriculae distributed in southern Chile are situated at the base of the cladogram and they are the sister group to both the Argentinian (A. claraziana, A. luteola, A. maculafulgens and A. millepunctata) and the Chilean species (A. grylloidea and A. crassa). The Biogeographic analysis using DIVA 1.1 found 1 optimal reconstruction that involves a vicariant event at each node. The vicariant event of the most apical node of the tree can be correlated to the uplifting of the Andes. The basal species are distributed in the southern regions of Chile and in the Patagonian Steppe, while the remaining species are distributed in northern highlands. Environmental Niche Models showed that the soil variable was important for all eight species. According to the models, A. claraziana and A. millepunctata have large potential geographic distribution covering almost all the Patagonian area, and have similar niche requirements, while the six remaining species showed a more restricted geographic distribution.